69.7k views
1 vote
Can someone help me with this question

Can someone help me with this question-example-1
User Marverix
by
5.3k points

2 Answers

5 votes

Answer:


(2)/(3) x + (1)/(3) - (1)/(3) x = (1)/(3) ( x - 1)\\\\ \\(4)/(3)x - (4)/(3) - (2)/(3) = (4)/(3) ( x - 1)\\\\( (1)/(3) x + (2)/(3) ) + ( -(2)/(3)x - (4)/(3)) = -(1)/(3) ( x + 2)\\\\((2)/(3)x + (1)/(3) ) + ((2)/(3) x - (2)/(3) ) = (1)/(3) ( 4x - 1 )

Explanation:

Simplify each equation by combining like terms, and then factoring


(2)/(3) x + (1)/(3) - (1)/(3) x

=
(1)/(3) x + (1)/(3)

=
(1)/(3) ( x + 1)


(4)/(3)x - (4)/(3) - (2)/(3)

=
(4)/(3)x - (6)/(3)

=
(4)/(3) ( x - 1 )


\ ( (1)/(3) x + (2)/(3) ) + ( -(2)/(3)x - (4)/(3))

=
-(1)/(3)x - (2)/(3)

=
- (1)/(3) x ( x + 2)


\ ((2)/(3)x + (1)/(3) ) + ((2)/(3) x - (2)/(3) )

=
\ (4)/(3)x - (1)/(3)

=
\((1)/(3) ( 4x - 1)

User Crismely
by
4.6k points
2 votes

Answer:

Explanation:


1)(2)/(3)x + (1)/(3)-(1)/(3)x = (2)/(3)x-(1)/(3)x +(1)/(3)\\\\\\=((2-1))/(3)x+(1)/(3)\\\\\\=(1)/(3)x+(1)/(3)\\\\\\=(1)/(3)(x+1)


2) (4)/(3)x-(2)/(3)-(2)/(3)=(4)/(3)x + ((-2-2))/(3)\\\\\\


=(4)/(3)x -(4)/(3)\\\\\\=(4)/(3)(x-1)


3) ((1)/(3)x+(2)/(3))+((-2)/(3)x-(4)/(3))=(1)/(3)x-(2)/(3)x+(2)/(3)-(4)/(3)


= (-1)/(3)x-(2)/(3)\\\\\\=(-1)/(3)(x+2)\\

4)
((2)/(3)x +(1)/(3))+((2)/(3)x-(2)/(3))=(2)/(3)x+(2)/(3)x+(1)/(3)-(2)/(3)


=(4)/(3)x-(1)/(3)\\\\\\=(1)/(3)(4x-1)

User Lapolonio
by
4.6k points